PIJAT BAYI SEBAGAI UPAYA PENINGKATAN BONDING ATTACMENT MELALUI PEMBERDAYAAN IBU DI POSYANDU BALITA DUSUN MONGGANG, SITIMULYO, PIYUNGAN, BANTUL - rahmah widyaningrum; Okta Risya Safitri (LPPM STIKES Madani Yogyakarta, 2019)
Posyandu Balita or integrated health service for under five age children in Dusun Monggang is a place of basic health activities organized from, by and for the community in the area. The program is conducted by health cadres assisted by local health workers. Posyandu Balita Monggang was chosen as a partner because it is one of the areas assisted by Madani STIKes in Yogyakarta for health services and education. Activities conducted at the Posyandu include: weighing children under five, filling in a record book for children’s growth and development namely KMS, consulting, providing supplementary food, and so on. This community service activity aims to provide understanding about infant massage to mothers who have babies and children under five age. Methods of community service activities include: examination of height and weight, assessment of maternal and infant characteristics and education of infant massage benefits and techniques using lecture techniques and giving leaflets. The results of the activity show that the characteristics of the baby, with a total of 10 babies, ranged in age from 0-18 months, the majority of men were 60% and all infants under five had good nutritional status (-2 up to +2 sd). While maternal characteristics include: age between 30-39 years (60%), final education Diploma / Bachelor (50%), and employment of the majority is housewife (90%). This activity is expected to be able to improve knowledge, attitudes and implementation of infant massage in an effort to improve bonding attachments of baby and mothers in Monggang.